Soil Thermophysical Properties Near the InSight Lander Derived From 50 Sols of Radiometer Measurements. Issue 8 (12th August 2021) - Piqueux, Sylvain; Müller, Nils; Grott, Matthias; Siegler, Matthew; Millour, Ehouarn; Forget, Francois; Lemmon, Mark; Golombek, Matthew; Williams, Nathan; Grant, John; Warner, Nicholas; Ansan, Veronique; et al.
Abstract: Measurements from the InSight lander radiometer acquired after landing are used to characterize the thermophysical properties of the Martian soil in Homestead hollow. This data set is unique as it stems from a high measurement cadence fixed platform studying a simple well‐characterized surface, and it benefits from the environmental characterization provided by other instruments. We focus on observations acquired before the arrival of a regional dust storm (near Sol 50), on the furthest observed patch of soil (i.e., ∼3.5 m away from the edge of the lander deck) where temperatures are least impacted by the presence of the lander and where the soil has been least disrupted during landing. Diurnal temperature cycles are fit using a homogenous soil configuration with a thermal inertia of 183 ± 25 J m −2 K −1 s −1/2 and an albedo of 0.16, corresponding to very fine to fine sand with the vast majority of particles smaller than 140 μm. A pre‐landing assessment leveraging orbital thermal infrared data is consistent with these results, but our analysis of the full diurnal temperature cycle acquired from the ground further indicates that near surface layers with different thermophysical properties must be thin (i.e., typically within the top few mm) and deep layering with different thermophysical properties must be at least below ∼4 cm. The low thermal inertia value indicates limited soil cementation within the upper one or two skin depths (i.e., ∼4–8 cm and more), with cement volumes <<1%, which is challenging to reconcile with visible images of overhangs in pits. Plain Language Summary: InSight carried a six‐channel radiometer used to measure diurnal surface temperatures over the duration of the mission. Surface temperatures are controlled by insolation and the microscopic physical properties of the soil (typical grain size, density, degree of soil cementation, or internal layering) that could not be resolved without a microscope or other instruments. Because the InSight lander does not have any systematic way to interrogate the soil, we have instead analyzed these temperature data and characterized the near‐surface soil properties. We found that the soil structure near the lander is homogeneous within the top few cm, and is made of loose sandy material with very little to no cementation. These properties are consistent with those derived from orbit before landing using remote sensing techniques, but difficult to reconcile with visible imagery showing evidence for induration farther from the hollow margin. Key Points: The InSight radiometers measured surface temperatures multiple times per sol over a flat and homogeneous patch of Martian soil The thermal inertia of the soil in Homestead hollow is ∼183 ± 25 J m −2 K −1 s −1/2, consistent with aeolian fine sand infilling The presence of a duricrust suggested by imagery is difficult to reconcile with this thermal inertia value